RETRACTED: Designing of SiO2 mesoporous nanoparticles loaded with mometasone furoate for potential nasal drug delivery: Ex vivo evaluation and determination of pro-inflammatory interferon and interleukin mRNA expression - Mehmood, Yasir; Shahid, Hira; Barkat, Kashif; Ibraheem, Muhammad; Riaz, Humayun; Badshah, Syed Faisal; Chopra, Hitesh; Sharma, Rohit; Nepovimova, Eugenie; Kuca, Kamil; Valis, Martin; Emran, Talha Bin (Frontiers in Cell and Developmental Biology, 2023)
The main objective of the current research work was to synthesize mesoporous silica nanoparticles for controlled delivery of Mometasone Furoate for potential nasal delivery. The optimized sol-gel method was used for the synthesis of mesoporous silica nanoparticles. Synthesized nanoparticles were processed through Zeta sizer, SEM, TEM, FTIR, TGA, DSC, XRD and BET analysis for structural characterization. In vitro dissolution test was performed for the inclusion compound, while the Franz diffusion experiment was performed for permeability of formulation. For the determination of expression levels of anti-inflammatory cytokine IL-4 and IL-5, RNA extraction, reverse transcription, and polymerase chain reaction (RT-PCR) were performed. MTT assay was also performed to determine the cell viability. Synthesized and functionalized mesoporous silica nanoparticles showed controlled release of drug. FTIR spectroscopy confirmed the presence of the corresponding functional groups of drug within mesoporous silica nanoparticles. Zeta sizer and thermal analysis confirmed the delivery system was in nano size and thermally stable. Moreover, a highly porous system was observed during SEM and TEM evaluation and further it was confirmed by BET analysis. The greater cellular uptake with improved permeability characteristics was also observed. As compared to the crystalline drug, a significant improvement in the dissolution rate was observed. It was concluded that stable mesoporous silica nanoparticles with significant porosity were synthesized, efficiently delivering the loaded drug without any toxic effect.